Autoignition and flame spectroscopy of propane mixture in a rapid compression machine. (1st December 2018) - Goyal, T.; Trivedi, D.; Samimi Abianeh, O.
Highlights: RCM, high-speed camera EMCCD and flame spectrometer were used. Several known and unknown excited radicals were identified during autoignition process. Detonation and deflagration were observed close to end of ignition delay duration. The propane mechanism were used to model the autoignition process. Spectroscopy of autoignition were performed at various conditions. Abstract: The autoignition process of propane has been studied using an optically accessible rapid compression machine (RCM). The ignition delay times of the fuel were measured at two compressed pressures of approximately 21 and 30 bar, equivalence ratios of 0.5, 0.8, 1.0 and 1.2, and at various compressed gas temperatures. A detailed kinetic model was also used to simulate the autoignition. A new methodology was also developed and discussed to include the effect of heat transfer in the mechanism model simulation. The combustion process imaging was acquired using high-speed camera and the deflagration like combustion with blue continuum spectrum was observed close to the end of ignition delay at all of the studied conditions, excluding the condition with very long ignition delay (e.g., 90 ms). The deflagration concluded with detonation for most of the studied conditions. The excited radicals' chemiluminescence emissions were acquired using flame spectrometer and Electron-Multiplying Charge-Coupled Device (EMCCD) with wavelength ranging from 280 nm to 700 nm. Several excited radicals were detected during autoignition process and their time-resolved intensity as a function of mixture conditions (pressure, temperature and equivalence ratio) were studied.